The synergistic role of Ni-Co bimetallic catalyst for H2-rich syngas production via glycerol dry reforming - Nor Shafiqah, Mohd-Nasir; Sumaiya, Zainal Abidin; Nurul Asmawati, Roslan; Osazuwa, Osarieme Uyi; Chanakaewsooboon, Issara (Elsevier Ltd, 2022)
A by-product of biodiesel manufacturing, glycerol, is known for its potential to generate syngas via the glycerol dry reforming (GDR) reaction. This study evaluates monometallic and bimetallic Nickel–Cobalt (Ni–Co) (with 15%Co, 3%Ni–12%Co, 4.5%Ni-10.5%Co, 7.5%Ni-7.5%Co, 10.5%Ni-4.5%Co and 15%Ni loading) on Alumina (Al2O3) support extracted from aluminium dross. The catalysts were prepared using an ultrasonic-assisted impregnation process and used in GDR at temperatures ranging from 873 to 1173 K at stoichiometric feed ratio. Analyses result showed that the diluting impact of Ni–Co bimetallic precursors resulted in a reduction of metal crystallite size and improved H2 and CO2 uptake. The conversion of glycerol and product yield were in the order of 3%Ni–12%Co/Al2O3 > 4.5%Ni-10.5%Co/Al2O3 > 7.5%Ni-7.5%Co/Al2O3 > 10.5%Ni-4.5%Co/Al2O3 >15%Co/Al2O3 > 15%Ni/Al2O3, with 3%Ni–12%Co/Al2O3 having values of 75.6%, 64.7% and 44.8%, for glycerol conversion, H2 and CO yield respectively. All catalysts achieved product ratios ranging from 1.20 to 1.44. The high oxygen vacancies in Ni–Co bimetallic catalysts aided the reduction of carbon formation. Enhanced Ni–Co particles dispersion on Al2O3 support reduced the agglomeration of metal particles, thus, creating smaller crystallite size. The changes in binding energy peaks of Ni and Co were indicative of strong electronic interaction which created Ni–Co bimetallic alloys. 3%Ni–12%Co was regarded as the best catalyst for this study since it was effective in enhancing the conversion of glycerol and product yield.